Representation of Women Leadership in Nussa and Rara Animation from the Question of Representation Perspective - Lisnawati, Lisnawati; Praptiningsih, Novi Andayani; Heryanto, Gun Gun; Bakti, Andi Faisal; Hayat, Heni (Communicare : Journal of Communication Studies, 2024)
This research examines gender representation in the animated series Nussa and Rara. It applies Gill Branston and Roy Stafford's "Questions of Representation" theory, which is elaborated into three concepts: stereotypes, gender representation, and positive and negative debates. The study adopts a descriptive qualitative approach, focusing on the character Umma (the mother) as the research subject, while the representation of female leadership in the show serves as the research object. The data analysis employs Roland Barthes' semiotic analysis technique, with the unit of analysis including visual elements such as angles, settings, and gestures. The findings reveal that female leadership in Nussa and Rara is portrayed through the character of Umma. The stereotypes associated with female leadership are reflected in her capabilities. Gender representation highlights Umma's feminine traits while also emphasizing her leadership qualities. On the positive side, Umma is depicted as a competent leader, free from harmful gender stereotypes. However, the representation remains limited. It is crucial to recognize that stereotypes, generalizations, and leadership abilities should be evaluated based on individual experiences and competence rather than preconceived notions.